Analisis Antrian dalam Pengoptimalan Pelayanan Stasiun Pengisian Bahan Bakar Umum (SPBU) dengan menggunakan Model Antrian Multi Channel Single Phase - Siallagan, Iren Laurensia; Sirait, Debora Exaudi; Br Sinaga, Juli Antasari (CV. Creative Tugu Pena, 2024)
Queues often occur in public services, one of which is gas station 14.211.203 Jl. D.I Panjaitan No.49 Pematangsiantar, where long queues occur at service facilities, especially in the type of pertalite fuel for motorcycle vehicles. The purpose of this study was to determine the analysis of the queuing system in optimizing services at SPBU 14.211.203 JL. D.I Panjaitan No.49 Pematangsiantar by using a multi-channel single phase queuing model. This type of research is descriptive quantitative. The queuing model applied to this gas station is a single channel single phase model. Based on the results of the study, it is known that with the queuing model applied, it can be said that the level of service at SPBU 13.211.203 is not optimal enough because the busy system utility (p) has a high percentage of the average number of customers waiting in the queue is 3 to 4 customers, The average time spent waiting in the queue is between 1 to 3 minutes, For the average time spent by customers while being served is between 2 to 3 minutes. For this reason, optimization suggestions are given that can be done, namely by using a single phase multi-channel queuing model which uses one service line with two service facilities, then the level of busy service facilities has a smaller percentage of busyness, which is below 50 %, the average level of busyness is below 50 %. Keywords: Queuing, Multi Channel Single Phase, Pertalite